Mechanical Properties and Resistance Coefficient of Carbon Steel during Fire. Issue 2 (1st September 2021) - Murakawa, Tomonori; Takahashi, Yusuke; Imagawa, Yusuke; Ohyama, Osamu
Abstract: Recently, serious fire accidents have occurred on bridges. For example, the 9‐Mile Overpass located near Detroit, MI, USA, experienced serious damage, where the steel‐concrete composite girder bridge fell down. To avoid future instances of such events, we need to understand the effect of the decrease in hardness of carbon steel during fire on structural characteristics, and to clarify the collapse mechanism of a bridge. Fifty years ago, the Japan Society of Steel Construction (JSSC) defined the mechanical properties of carbon steel up to 900 °C. However, recently, there have been bridge fire incidents where the heat has exceeded an estimated 1000 °C. Therefore, it is necessary to conduct the high temperature tensile test above 900 °C. In Japan, the design method has changed from the allowable design method to the limited design method, and a fire design method for the safety, serviceability and restorability of bridges has not been established. In near future, we seek to clarify the resistance coefficient for fire design. Herein, we carry out the high temperature tensile test to determine the relationship between strength and temperature, and propose a resistance coefficient for fire design based on these results. The 1 % yield strength of SM400 (minimum tensile stress: 400 N/mm 2 ) decreased on average by 26 % at 500 °C, and on average by 94 % at 1100 °C. It was found that the elongation of carbon steel is greatest at 800 °C.